Adobe Dreamweaver CS5 on demand - Johnson, Steve, 1961- (On demand (Indianapolis, Ind.), 2010)
Need answers quickly? Adobe Dreamweaver CS5 on Demand provides those answers in a visual step-by-step format. We will show you exactly what to do through lots of full color illustrations and easy-to-follow instructions. Includes Workshops ACE Exam Objectives More than 600 Essential Dreamweaver CS5 Tasks Inside the Book: Understand and use the latest web technologies to create sites; Choose the right site structure and layout for sites; Create and use web page templates to quickly create pages; Use the simplified site setup to create and work with sites; Use Live view to design your web pages under real-world conditions; Create and maintain Cascading Style Sheets (CSS); Use coding tools to develop consistent and reusable code; Insert Adobe Photoshop files to create image Smart Objects; Manage collaboration with multiple developers; Use Subversion to manage different site versions; Manage local, remote, and testing sites; Transfer, synchronize, and validate sites Bonus Online Content Register your book at queondemand.com to gain access to: Workshops and related files and Keyboard shortcuts.